2021
DOI: 10.1177/016146812112300102
|View full text |Cite
|
Sign up to set email alerts
|

The Centrality of Critical Agency: How Asian American College Students Develop Commitments to Social Justice

Abstract: Context Systemic oppression is one of the most pressing problems in U.S. society. However, relatively little is known about the process by which college students become committed to social justice agendas. In addition, systematic empirical inquiries that examine how Asian American students, in particular, develop such commitments are difficult to find. Purpose/Research Question This inquiry was focused on understanding the process by which Asian American college students develop commitments to social justice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…While existing stereotypes of Asian Americans suggest that they are uniformly assimilationist and apolitical [25], Asian American Studies literature documents a long history of Asian American activism in U.S. society broadly and on college campuses specifically [26,36]. Yet, only a handful of higher education scholars have examined Asian American students' engagement in social justice efforts in higher education [10,[49][50][51][52][53]. This research provides some initial evidence regarding the factors that catalyze Asian American students' engagement in social justice agendas, as well as how these efforts lead to outcomes, such as stronger identity development, critical agency, and capacities to give back to their communities and society [10,[49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While existing stereotypes of Asian Americans suggest that they are uniformly assimilationist and apolitical [25], Asian American Studies literature documents a long history of Asian American activism in U.S. society broadly and on college campuses specifically [26,36]. Yet, only a handful of higher education scholars have examined Asian American students' engagement in social justice efforts in higher education [10,[49][50][51][52][53]. This research provides some initial evidence regarding the factors that catalyze Asian American students' engagement in social justice agendas, as well as how these efforts lead to outcomes, such as stronger identity development, critical agency, and capacities to give back to their communities and society [10,[49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, only a handful of higher education scholars have examined Asian American students' engagement in social justice efforts in higher education [10,[49][50][51][52][53]. This research provides some initial evidence regarding the factors that catalyze Asian American students' engagement in social justice agendas, as well as how these efforts lead to outcomes, such as stronger identity development, critical agency, and capacities to give back to their communities and society [10,[49][50][51][52][53]. The current inquiry extends this literature as one of the first empirical inquiries into the nature of their experiences engaged in social justice efforts, and likely the first empirical analysis of the role of solidarity in their activism and advocacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on critical agency among Asian Americans and racial‐ethnic socialization in Asian American and Black American families suggest that these questions may be worth examining. Museus (2021) found that, among Asian American college students, parents' and siblings' critical action for social justice causes was highly influential for students' development of critical agency. Among Asian Americans, Juang et al (2018) found that some second‐generation Asian American parents felt empowered to engage in racial‐ethnic socialization, specifically because their parents did not talk to them about race.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Previous research has examined how race-related stress influences ethnic–racial identity (ERI; Iwamoto & Liu, 2010), the role of ERI in ethnic–racial discrimination (ERD; Yip et al, 2022), temporal sequencing of ERI and ERD (Gonzales-Backen et al, 2018), and ERI’s mediating role in ERD (Brittian et al, 2015; see Yip et al, 2019, for review). Previous research has also shown that ERI and discrimination may mobilize Asian Americans’ civic engagement (Museus, 2021; Phoenix & Arora, 2018). Vulnerability to cultural stress may increase awareness of inequality, ultimately predicting greater civic engagement (Moore et al, 2016; Plummer et al, 2022).…”
mentioning
confidence: 98%